Oral Administration of Heat-Killed Multi-Strain Probiotics Confers Durable Protection Against Antibiotic-Resistant Primary and Recurrent Urinary Tract Infections in a Murine Model - Bo-Yuan Chen; Zhen-Shu Liu; Yu-Syuan Lin; Hsiao Chin Lin; Po-Wen Chen (Antibiotics, 2025)
Background/Objectives: Alternative therapies for urinary tract infections (UTIs) have been explored, but their efficacy remains inconsistent. With rising antibiotic resistance, this study aimed to evaluate simplified postbiotic formulations derived from heat-killed probiotics for long-term protection against primary and recurrent UTIs in a murine model. Methods: We compared a multi-strain (seven-strain) versus a single-strain postbiotic in preventing Escherichia coli-induced UTIs and recurrent polymicrobial UTIs, assessed protection persistence after treatment discontinuation, and established a novel sustained UTI model via intravesical co-inoculation of three uropathogens. Mice were allocated to three experimental groups: a placebo group (PBS), Postbiotic I group (a seven-strain heat-killed probiotic formulation), and Postbiotic II group (a single-strain heat-killed probiotic). After two weeks of treatment, mice were challenged with uropathogenic E. coli (UPEC) and treated for seven days. Following a 14-day washout and bacterial clearance, they were rechallenged with multidrug-resistant UPEC, Klebsiella pneumoniae, and Staphylococcus pseudintermedius. Results: Both postbiotics significantly accelerated bacterial clearance in primary UTIs (p < 0.05). In recurrent UTIs, placebo-treated mice exhibited persistent bacteriuria, while Postbiotic I maintained a significantly higher sterile urine rate (50–80%, p < 0.01) post-treatment. Histopathological analysis confirmed reduced bladder and kidney inflammation (p < 0.05) with Postbiotic I. Conclusions: These findings demonstrate the superior efficacy of Postbiotic I in mitigating UTIs, with sustained protection post-treatment, supporting its potential as a long-term, non-antibiotic strategy. Additionally, our reproducible chronic UTI model, achieved through the co-inoculation of three uropathogens, provides a valuable tool for future research on chronic UTI pathogenesis and treatment.